Combined Cerebellar and Spinal Cord Deficits Caused by an Underlying Gynecologic Malignancy. (9th January 2020) - Othman, Tamer; Hendizadeh, Moshe-Samuel; Vankina, Ritika; Park, Susan; Kim, Phyllis
Abstract : Paraneoplastic cerebellar degeneration (PCD) is an uncommon autoimmune disorder targeting antigens within the nervous system and is usually associated with an underlying malignancy. Neurologic symptoms frequently precede the cancer diagnosis, which is most often seen in women with breast or gynecologic tumors. Anti-Yo-related PCD is the most common PCD syndrome, and one of the best understood. Although cerebellar signs are characteristic of anti-Yo PCD, myelopathy is an unusual presentation of anti-Yo PCD based on published case series and reports. Unfortunately, the prognosis for anti-Yo PCD is often poor, and most patients become bedridden. We report a case highlighting a severe presentation of cerebellar degeneration along with an unusual finding of myelopathy in a patient with a newly diagnosed gynecologic cancer.